1992
DOI: 10.1152/ajpcell.1992.263.3.c667
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an InsP3-gated channel protein in isolated rat olfactory cilia

Abstract: Stimulation of rat olfactory cilia (ROC) with odorants leads to a transient elevation in the levels of either cAMP or inositol trisphosphate (InsP3). We have characterized the binding of [3H]InsP3 to isolated ROC. Unlabeled InsP3 displaced [3H]InsP3 binding in a dose-dependent manner (dissociation constant = 3.9 +/- 0.65 microM). Binding was stereospecific and dependent on the number of phosphates in the inositol ring. A ciliary protein of 120 kDa molecular mass was labeled specifically upon exposure of cilia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 28 publications
6
28
1
Order By: Relevance
“…The fact that Ruthenium Red (RR) did not significantly alter chemosignal-activated currents may suggest that IP 3 R3 is not localized to the plasma membrane as has been demonstrated in cilia of olfactory sensory neurons (Fadool and Ache, 1992;Restrepo et al, 1992;Cunningham et al, 1993;Honda et al, 1995;Cadiou et al, 2000). These data, however, fail to reveal whether IP 3 R3 is an important member of the signal transduction scaffold.…”
Section: Discussionmentioning
confidence: 98%
“…The fact that Ruthenium Red (RR) did not significantly alter chemosignal-activated currents may suggest that IP 3 R3 is not localized to the plasma membrane as has been demonstrated in cilia of olfactory sensory neurons (Fadool and Ache, 1992;Restrepo et al, 1992;Cunningham et al, 1993;Honda et al, 1995;Cadiou et al, 2000). These data, however, fail to reveal whether IP 3 R3 is an important member of the signal transduction scaffold.…”
Section: Discussionmentioning
confidence: 98%
“…Solid functional information on IP 3 -gated channels in the plasma membrane has mostly been obtained in olfactory neurons isolated from numerous species (see e.g. Fadool and Ache, 1992;Restrepo et al, 1992;Munger et al, 2000;Cadiou et al, 2000). More recent work confirmed that various cell types, including Jurkat lymphocytes, express significant amounts of the various IP 3 R isoforms (5-23% of their total amount) in their plasma membrane (Tanimura et al, 2000).…”
Section: Plasma Membranementioning
confidence: 99%
“…It therefore had to be assumed that both second messengers, cAMP and InsP 3 , directly regulate Ca 2+ permeability of the ciliary membrane (Bruch, 1996;Restrepo et al, 1996;. This was supported by an increasing number of studies demonstrating InsP 3gated cation channels in the plasma membrane of olfactory neurons (Cunningham et al, 1993;Honda et al, 1995;Kalinoski et al, 1992;Kaur et al, 2001;Lischka et al, 1999Lischka et al, , 1995Okada et al, 1994;Restrepo et al, 1990Restrepo et al, , 1991Restrepo et al, , 1992Smutzer et al, 1997).…”
Section: Is Insp 3 An Alternative Second Messenger In Olfaction?mentioning
confidence: 99%